FRASEOLOGIA E ANTROPONÍMIA: DA TEORIA A UMA PRÁTICA EXPLORATÓRIA DE UNIDADES FRASEOLÓGICAS E CULTUREMAS ANTROPONÍMICOS - Marçalo, Maria João (Revista de Letras, 2024)
Abstract The objective of this article is to present a list of jocular and pejorative designations of collective identities or nicknames, of an anthroponymic nature, relating to toponyms in the district of Évora in Portugal. In this text, we utilise the corpus compiled by the anthropologist João David de Morais and published in 2006 in the book Ditos e Apodos Colectivos. The relationship between language and culture is a complex one, extending from the concept of language as a repository of human cultural manifestations to the notion that words are carriers of world views. Language, therefore, can be seen as a means of accessing culture. In order to fully comprehend this relationship, it is essential to understand language, culture and identity, taking into account the lexical manifestations presented in historical and regional contexts. In this article, we will make a modest contribution to the study of phraseology. This line of thinking posits that lexical realizations, particularly those pertaining to social activities, play a pivotal role in comprehending the cultural nuances of a given people and in the formation of a distinctive or regional identity. The cultural themes encapsulated in the nicknames, apodos, and collective designations under examination here contribute to the construction of an identity. The following keywords are used throughout this text: phraseology, anthroponymy and toponymy. Keywords: Phraseology, anthroponymy, toponymy